Oral bisphosphonate use reduces cardiovascular events in a cohort of Danish patients referred for bone mineral density - Rodriguez, AJ; Ernst, MT; Nybo, M; Prieto-Alhambra, D; Ebeling, PR; Hermann, AP; Abrahamsen, B (Oxford University Press, 2020)
Context: The cardiovascular (CV) safety of oral bisphosphonates (oBP) is uncertain. Objective: Determine the risk of CV events in oBP users referred for bone mineral density (BMD) testing compared with matched controls. Design: Cohort study. Setting: Danish national prescription registry enriched with local hospital data from Odense. Participants: Individuals aged ≥45 years referred for BMD testing. Exposure: Oral BP. Outcomes: Hospitalization for any CV event. Secondary study outcomes were specific CV events. Negative (inguinal hernia surgery and ingrown toenail) and positive (fragility fracture) control outcomes assessed systemic bias. Cox proportional hazards models were fitted to estimate hazard ratios (HR) [95% confidence intervals]. Results: There were 2,565 oBP users (82.6% women) and 4,568 (82.3% women) propensity score-matched controls. Alendronate accounted for 96% of oBP prescription. A total of 406 (15.8%) CV events occurred in oBP users (rate = 73.48 [66.67 to 80.98]); and 837 (18.3%) events in controls (rate = 104.73 [97.87 to 112.07]) with an adjusted HR of 0.68 [0.60 to 0.77]. Additional adjustment for BMD did not attenuate estimates [HR of 0.67 (0.58 to 0.78)]. Similar results were seen for secondary outcomes where risk reductions were seen regarding atrial fibrillation, stroke, heart failure and aneurysms. Positive and negative control outcome analyses identified minimal residual confounding. Conclusion: Oral BP users experienced a 33% reduced risk of CV events. This observational real-world study adds to a growing body of evidence for cardio-protection by oBP that warrants testing in a randomized setting.